KEGIATAN KKN TEMATIK DENGAN PENDAMPINGAN BELAJAR, BERMAIN DAN SOSIALISASI KESEHATAN PADA ANAK USIA SEKOLAH MASA PANDEMI COVID-19 - Annisa Fatmawati; Khasanah Nur Hidayah; Hana Asti Pradesa; Israwani; Lusita Diah Pertiwi; Nun Ulya Kencana; Sumarni; Sukma Elennia; Vibriani Amrin; Wahyu Fajar Irianti (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The Covid-19 pandemic has had an impact on all fields, especially in the fields of health and education. The government issued a circular regarding the implementation of distance learning to prevent the transmission of the corona virus. In connection with the holding of the Thematic KKN (kuliah kerja nyata) in Koripan Hamlet, Sindumartani, Slema, the work program for KKN activities is in the form of learning assistance, playing and health socialization. This work program is expected to be useful for students and parents. This mentoring activity includes several activities, including helping direct the preparation of children's school assignments, assisting children in understanding school subject matter and knowledge about health and playing with dance and other media. The head of Koripan Hamlet and parents appreciate the KKN students who have provided assistance so that this activity of mentoring school-age children can add insight in order to develop cognitive, affective and psychomotor.